Effect of weedy rice (Oryza sativa L.) on the yield of cultivated rice (Oryza sativa L.) in greenhouse and field environment - Salmah Tajuddin
This study aimed to investigate the competitive abilities of cultivated rice (CR) and weedy rice (WR). This study was performed over a period of twelve months from January 2012 to December 2012 in greenhouse and field environments. MR220, MR220 CL1, MR211, and Setanjung were the selected CR varieties used in the greenhouse study. The field study was simultaneously conducted using the same selected CR varieties as the greenhouse study. However, only one type of CR variety was planted in the field study because of time, space and labor constraints. MR220 CL2 was selected because of its high yields and short maturity period among all the CR varieties. Specific proportions or WR and CR were planted in pots for the greenhouse study plots for the field study based on additive series and replacement series designs. The competitive abilities of CR varieties were measured based on the Relative Growth Rate (RGR), Relative Yield, and linear regression analysis under different infestation densities of WR. Results of additive series and replacement series designs indicate that CR varieties were less competitive than WR. Different CR varieties demonstrated various competitive abilities. The presence of WR in CR decreased overall RGR, yield components, and yield. WR significantly (P<0.05) affected RGR, culm height, number of tiller, number of filled grain, straw weight, 1000 grain weight, and yield of CR varieties. The new CR variety (MR220 CL2) demonstrated high yield, but is was less competitive than WR and other old rice varieties.